Principais ingredientes ativos dos agroquímicos: aplicação e uso no Brasil - Souza, José Lucas de (Universidade Federal de São Carlos, 2023)
This research aimed to present (identify) which are the main active ingredients (AI) used in the formulation of pesticides, as well as their use (utility/importance) in agronomy and possible socio-environmental impacts inherent to improper use. To this end, a systematic literature review was carried out as a research strategy, mapping studies and gathering data from university repositories, books and websites of bodies involved in the subject, such as IBGE, MAPA, IBAMA, WHO. From this, it was found that the most commercialized (IA) in 2022 were: Glyphosate, 2,4-D, Mancozeb, Chlorothalonil, Atrazine, Acephate, Malathion, Clethodim, Agricultural sulfur and S-metolachlor. The Brazilian regions that most used these pesticides in 2020 were: Midwest (34.57%), South (22.52%), Southeast (20.96%), Northeast (9.34%) and North (5. 03%). These active principles are important for Brazilian agriculture and have different uses in agronomy, but all products formulated based on these actives present risks to human and environmental health. Of the three most used (IA), 2,4-D and Mancozeb are classified as extremely toxic to human health, while the other actives fall into the moderately toxic class (chlorothalonil, atrazine, acephate and S-metolachlor) and little toxic (Glyphosate and Malathion) or unlikely to cause acute harm (Cletodim and Sulfur). Damage to the environment varies for each (IA), according to its behavior in the soil, water currents, air and animals, but all pesticides have the potential to harm the environment. In view of this, it was evident that the regions with the largest monocultures are the largest consumers and there is a need to find a balance between the use of these products and the minimization of their impacts, given their importance for food production and the consequences of their use inappropriate.
Main active ingredients of agrochemicals: application and use in Brazil
Keywords: Agricultura; Agrotóxicos; Produção agrícola; Saúde; Ambiente; Agriculture; Pesticides; Agricultural production; Health; Environment; CIENCIAS AGRARIAS::AGRONOMIA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA AGRARIA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA DOS RECURSOS NATURAIS